Music at the intersection of Brazilian culture - Dekaney, Elisa Macedo, 1966- author.
1 online resource
Keywords: Music at the Intersection of Brazilian Culture takes an interdisciplinary approach by utilizing several aspects of Brazilian music, race, and food as a window to understanding Brazilian culture, with music at the core. Through a holistic understanding of the Brazilian experience - exploring issues of race, colonization, sustainable development, and the contributions of the three distinct ethnic groups in the making of Brazil - the authors create a narrative based on their own recollection of memories, traditions, customs, sounds, and landscapes that they experienced in Brazil. Each engaging section begins with an overview of the topic that places it in historical context, and then focuses on each subtopic with a thorough presentation of the content as well as suggested activities that can be implemented in the classroom. The chapters conclude with a list of useful references, resources, and audio recording examples, which are available on Spotify, to present readers with a musical landscape of the folktales. These can be found online via the Routledge catalogue page for this book. This book is an essential resource for students and teachers of music and cultural studies, as it unpicks complex issues to help readers better understand and appreciate Brazilian culture.